A RIGHTS-BASED APPROACH TO HANDLING COMMUNITY POVERTY IN FOREST AREAS (CASE STUDY IN PARUNGMULYA VILLAGE, CIAMPEL DISTRICT, KARAWANG REGENCY) - Hajbudin Hekmatiar; Risna Resnawaty; Hery Wibowo (RADJA PUBLIKA, 2026)
Resource-rich forests often become places where poor communities gather. Current forestry policies have not fully addressed poverty. This study examines the extent to which the Social Forestry Program, through the Social Forestry Forest Utilization Permit (IPHPS) scheme, can fulfill the rights of poor communities in forest areas. This study examines program achievements not only from an economic perspective but also from the perspective of fulfilling human rights (HAM). This study uses a qualitative approach with a single case study in Parungmulya Village, Ciampel, Karawang. This area borders the Mitra industrial area (KIM), which is in stark contrast to the conditions of the community within the forest area. Data collection techniques used were participant observation and document collection, which were then analyzed and verified through triangulation. The analytical framework uses structural poverty theory, a Rights-Based Approach (HRBA) with the PANEL principle (Participation, Accountability, Non-discrimination, Equity, Legality) from a Social Work Perspective. The results of the study indicate that the Social Forestry program can restore the dignity and legal status of communities from